2017
DOI: 10.1111/jzo.12504
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of diurnal rest site selection by spotted hyaenas

Abstract: Rest sites are key locations to many animals but their selection has been poorly studied in large carnivores. We investigated seasonal diurnal rest site selection by spotted hyaenas (Crocuta crocuta) in Hwange National Park, Zimbabwe. We assessed the effects on hyaena diurnal rest site selection of (1) distance to the nearest waterhole, as waterholes can be considered prey hotspots in the study ecosystem, (2) habitat type and vegetation characteristics, in particular visibility as it influences detection risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Likewise, Bender et al [15] reported fine-scale habitat segregation among pumas (Puma concolor), coyotes (Canis latrans) and bobcats (Lynx rufus) in the San Andres Mountains as a result of preferences for habitat characteristics that facilitate movements, despite being positively associated with one another. Thus, our results lends support to a growing body of evidence that demonstrates coexistence among carnivores is facilitated by behavioural mechanisms, in addition to spatial and temporal partitioning [15,31,51,114,115].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Likewise, Bender et al [15] reported fine-scale habitat segregation among pumas (Puma concolor), coyotes (Canis latrans) and bobcats (Lynx rufus) in the San Andres Mountains as a result of preferences for habitat characteristics that facilitate movements, despite being positively associated with one another. Thus, our results lends support to a growing body of evidence that demonstrates coexistence among carnivores is facilitated by behavioural mechanisms, in addition to spatial and temporal partitioning [15,31,51,114,115].…”
Section: Discussionsupporting
confidence: 83%
“…Our results indicate that hyenas in Chobe spent more time in areas that were closer to permanent water and had increased recursion to locations further from water. Spotted hyenas have been found to use locations far from water for den sites and resting [30, 114], thus we suggest that hyenas are potentially choosing to remain in areas with landscape characteristics that minimizes detection [120] while increasing prey vulnerability [121]. Although spotted hyenas require access to drinking water, they can survive on very little of it [38].…”
Section: Discussionmentioning
confidence: 99%
“…Carnivores that are in the same guild coexist through resource partitioning, with dietary separation being an important factor in facilitating niche separation (Vieira & Port, 2007; Kamler et al, 2012). Behavioural and spatial separation may also facilitate coexistence (Kushata et al, 2018) via different activity peaks (Kamler et al, 2012), foraging behaviour (Périquet et al, 2016), selection for different prey size classes (Purchase, 2004), and segregation of generalist and specialist feeding strategies (Périquet, Fritz & Revilla, 2015). Understanding the relative impacts of carnivores on prey species would help to prioritize management interventions to mitigate population declines.…”
Section: Introductionmentioning
confidence: 99%
“…Such differences might reflect individuals moving away from the roads, where the latrine camera traps were located, as well as away from the communal den sites, into more secluded areas for use as daytime resting sites during that time. The opposite was found to be true for spotted hyaena in Hwange National Park (Kushata et al 2017); spotted hyaena preferred resting sites close to the roads which was attributed to roads benefitting cursorial predators by allowing them to move faster through an area, and the lack of tourism activity on the roads during the study period. In contrast, brown hyaenas are predominantly scavengers (Mills 1990), and our study period coincided with the high peak of tourism activity on ONR.…”
Section: Discussionmentioning
confidence: 90%